IDENTIFICATION OF CONCENTRATE QUALITY FROM LOCAL RAW MATERIALS THROUGH HEMATOLOGY PROFILE ON BALI CATTLE - Kertawirawan, I Putu Agus; Budiari, Ni Luh Gde; Adijaya, I Nyoman; Kusumadewi, Made Rahayu (Buletin Veteriner Udayana, 2022)
Innovation in the use of local feed is an alternative to reducing production costs in livestock business. However, feeding at different levels will affect physiological conditions such as differences in blood counts This study was conducted to determine the quality of concentrate made from local raw materials toward rice bran through a hematological profile. The observed hematological parameters were total erythrocyte, hemoglobin level, and hematocrit value. The treatment given was P0 = group of cattles that were given green feed plus 1 kg of rice bran/cattle/day; P1 = group of cattles given forage plus 1 kg of concentrate (50% substitution of corn waste and peanut shells); P2 = group of cattles given forage plus 1 kg/cattle/day of concentrate (75% substitution of corn waste and peanut shells). This study used a randomized block design. Blood is drawn through the jugular vein using a venoject. Total erythrocytes, hemoglobin levels and hematocrit values were calculated using the routine hematology examination method with a Hematology Analyzer machine. The results showed that the provision of additional feeds in the form of bran and concentrate made from local raw materials to weaning Bali cattle had no significant effect (P>0.05) on total erythrocytes, hemoglobin levels, and hematocrit values. These results indicate that concentrate made from local raw material has the potential as an alternative feed to replace rice bran without affecting the physiological conditions of the cattle.